TEMPERATURE RISE UNDER THE PLATE OF A HIGH POWER SEISMIC VIBRATOR - Khudzinskiy L.L. (My University, 1990)
On a suggestion of A.V. Nikolayev, our Institute is developing and testing a new method for the detailed study of wave fields, involving the combined use of seismic and thermal measurements. In the first stage of this development we aimed at producing a high-sensitivity temperature sensor capable of meeting the special requirements for such instruments. We then wanted to use this sensor in experimental studies designed to detect and measure the above-postulated phenomenon, and to see how valid these measurements are, since we assumed a priori that the temperature rise will be small and difficult to extract from the background of thermal noise. Our prototype quartz thermometer has the required sensitivity and accuracy and can be used for various theoretical and applied problems in geophysics. We have detected for the first time a significant temperature rise at a depth of 1.1 m under the vibrator plate. The plots show unambiguously that most of the rise in temperature results from heat liberation in the vicinity of the sensor; there are also much slower changes in temperature resulting from the heat conduction through the ground.